Medical app minefield: radiologists use of medical apps for education and reporting and do they require regulation?. Issue 10 (October 2021) - MacCormick, A.; Jenkins, P.; Roobottom, C.
Abstract : AIM: To evaluate the use of apps in radiology and consider advised changes to practice. MATERIALS AND METHODS: A survey was conducted of all radiology consultants and specialty trainees within Devon and Cornwall. The responses were collated, including the list of all medical applications used. These were assessed using the Medicine & Healthcare Products Regulatory Agency (MHRA) "Medical device stand-alone software including apps" guidance. RESULTS: The response rate was 88/150 (59%) radiologists who responded with the majority 48/88 (54.4%) using apps. Forty-four of 66 (67%) states that they did not assess the reliability or accuracy of these devices prior to use with 71/81 (88%) indicating that they were unaware of any regulations. Thirty-three items were identified of which 27 functioning apps were identified and three of these were considered medical devices and did not have complete and recognisable CE marking as required by the MHRA. CONCLUSION: This study highlights that application use is widespread. The vast majority of these applications are not considered medical devices; however, there are some devices that, according to the MHRA flow chart, are used in a way that classifies them as medical devices and should therefore be CE marked. This highlights the need for guidance and regulation of the medical application market with recommendations provided. Highlights: There are myriads of apps available to support and educate the radiologist. Some apps are considered medical devices, but do not have the appropriate regulation. Guidance on app usage, including medical devices and reference tools is required.